The society and the journal: Making interdisciplinarity a special issue in the life sciences (2020)
The Royal Netherlands Society for Agricultural Sciences (Koninklijke Landbouwkundige Vereniging, KLV, founded in 1886) took the initiative to publish the Netherlands Journal of Agricultural Science (NJAS) in 1953. In 2002, NJAS broadened its scope and was titled: NJAS–Wageningen Journal of Life Sciences. After 134 years, the general assembly of members decided to dissolve the Society in 2020. The end of the Society will not be the end of its journal. This paper presents a brief history of the Society and the journal, which exposes how the Society’s journal, originally strongly anchored in the plant sciences and agronomic research in the Netherlands, evolved towards an international journal with an increasingly strong interdisciplinary scope. The brief history signifies the crucial role of special issues as a collaborative endeavour and learning environment for making interdisciplinary approaches work.